Archaelogical provenancing of marble by pore size analysis, using phase transition porosimetry - Öztürk, M. Kaan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 1999)
Determination of the source of a particular marble sample is an ongoing subject of study among archaeometrists. In this study, categorization according to pore size distribution is suggested. The employed method for pore size analysis is Phase Transition Porosimetry (PTP). The principles on which PTP works are described. PTP requires a computer system for data taking and data processing. The electronic data-acquisition system and the control software are discussed extensively. After construction of a dilatometric Phase Transition Porosimeter, marble samples collected from field have been studied with this method and the results are given. The precision of PTP in low-porosity materials are discussed using the results.
Keywords: Marble -- Analysis.; Porosimeters.